Neuroinflammation is a susceptibility factor in developing a PTSD-like phenotype - Shanazz, Khadijah; Nalloor, Rebecca; Lucas, Rudolf; Vazdarjanova, Almira (Frontiers in Behavioral Neuroscience, 2023)
Post-Traumatic Stress Disorder (PTSD) is a psychological disorder that occurs after a traumatic event in a subset of exposed individuals. This implies the existence of susceptibility factors that foster the development of PTSD. Susceptibility factors are present before trauma and can contribute to the development and maintenance of PTSD after trauma. Manipulation of susceptibility factors may decrease the probability of developing PTSD. A putative susceptibility factor is inflammation. Patients with PTSD have been documented to have a higher pro-inflammatory profile compared to non-PTSD subjects. In addition, they are more likely to develop and die from cardiovascular disease which has a strong inflammation component. It is not known, however, whether inflammation plays a role in developing PTSD or whether reducing inflammation can prevent PTSD. Using the Revealing Individual Susceptibility to a PTSD-like phenotype (RISP) model, which classifies male rats as resilient or susceptible before trauma, we tested whether inflammation represents a susceptibility factor for PTSD. We found elevated IL-6 levels in the pre-frontal cortex of susceptible rats compared to resilient animals before trauma, but this was not the case in serum. These findings support the hypothesis that neuroinflammation, rather than systemic inflammation is a susceptibility factor for PTSD and implies that inflammation is neurogenic in its pathogenesis. Because we did not find this difference in serum it is unlikely that one can infer susceptibility to developing PTSD using peripheral markers of inflammation in the RISP model.